2013
DOI: 10.1177/1750635213479206
|View full text |Cite
|
Sign up to set email alerts
|

Facing the past: Media framing of war crimes in post-conflict Serbia

Abstract: Although it is generally acknowledged that national elites and the mass media play an important role in the way that societies come to terms with a legacy of war crimes, there is little empirical knowledge about whether and how the mass media actually do contribute to a process of 'facing the past'. Based on the case of Serbia, this study examines press media coverage of war crimes and war crime judiciary during the country's recent post-war period. Adopting a novel approach to the conceptualization and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Second, media have a ‘role in transitional justice process itself, by negotiating issues of identity’ (Price and Stremlau, 2012: 1077). Within this role, disregarded by most transitional justice scholars, journalists and media can have positive or negative impacts, by perpetuating hatred, inflaming identity politics or working towards peace (Golčevski et al, 2013: 120; Herfroy-Mischler, 2016: 826; Price and Stremlau, 2012: 1080). Truth commissions, international trials and public apologies ‘are reported as “media events”’ where journalists ‘are considered professional witnesses’ (Herfroy-Mischler, 2016: 826), having the ‘historic opportunity to write revised drafts of a well-known history that is continually being updated’ (Herfroy-Mischler, 2016: 826).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, media have a ‘role in transitional justice process itself, by negotiating issues of identity’ (Price and Stremlau, 2012: 1077). Within this role, disregarded by most transitional justice scholars, journalists and media can have positive or negative impacts, by perpetuating hatred, inflaming identity politics or working towards peace (Golčevski et al, 2013: 120; Herfroy-Mischler, 2016: 826; Price and Stremlau, 2012: 1080). Truth commissions, international trials and public apologies ‘are reported as “media events”’ where journalists ‘are considered professional witnesses’ (Herfroy-Mischler, 2016: 826), having the ‘historic opportunity to write revised drafts of a well-known history that is continually being updated’ (Herfroy-Mischler, 2016: 826).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, in post-conflict societies now democratically governed, journalists and the media are, at least by some, expected to play an important role in transitional justice processes, especially in the deconstruction of dominating versions of history in order to construct new narratives more aligned with public interest (Golčevski et al, 2013: 120).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-conflict news production, finally, is still influenced by the existing conflict context (see Golcevski et al, 2013). However, the routines and modes of journalism that are predominant in a non-conflict situation return gradually as the process toward non-conflict status continues.…”
Section: News Productionmentioning
confidence: 99%
“…As a result, insights that potentially damage the positive image of parts of society may not be published. Secondly, self-censorship might be connected to the often present state of democratic and economic transition that follows a violent conflict (Breuning and Ishiyama, 2007; Golcevski et al, 2013; Stremlau, 2013). Post-conflict societies emerging from a civil war often lack democratic civil societies.…”
Section: Introductionmentioning
confidence: 99%